1978
DOI: 10.1017/s0021859600056604
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilizer on growth and yield of semi-dwarf and tall varieties of winter wheat

Abstract: Eight amounts of nitrogen ranging from 0 to 210 kg N/ha were applied to two tall and one semi-dwarf variety of winter wheat in the spring of 1975 and 1976. The tall varieties were Cappelle-Desprez and Maris Huntsman; the semi-dwarf variety was Maris Fundin in 1975 and Hobbit in 1976. Interactions between varieties and nitrogen were few and small compared with the main effects. All varieties produced their maximum grain yields with 180 kg N/ha. The yield of the semi-dwarf varieties, but not the others, decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Under favourable growing conditions, starch and protein build up simultaneously and protein content may vary by 卤2% (Pearman et al 1978;Halloran 1981). Water stress and high temperature during the grain-filling period hinder the conversion of sucrose into starch but have less effect on protein formation (Brooks et al 1982;Bhullar and Jenner 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Under favourable growing conditions, starch and protein build up simultaneously and protein content may vary by 卤2% (Pearman et al 1978;Halloran 1981). Water stress and high temperature during the grain-filling period hinder the conversion of sucrose into starch but have less effect on protein formation (Brooks et al 1982;Bhullar and Jenner 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have been made of an inverse relationship between grain yield and protein content in wheat (Haunold et al 1962; Thorne and Blacklock 1971 ;Pearman et al 1978). This inverse relationship most probably arises from competition between the demands of protein synthesis for carbon, most likely as carbohydrate, and those of normal catabolism for carbon frameworks in the form of organic and keto acids (Steward and Durzan 1965).…”
Section: Introductionmentioning
confidence: 99%
“…SylvesterBradley and Kindred (2009) evaluating efficiency of N use and harvest index of this nutrient, explain that there are few data available about N use in cereals different genetically, however it is known that since the introduction of semi dwarf plants, these values have been modified. Pearman et al (1978) applied eight N doses in wheat plants, tall and semi dwarf, and observed that in plants with dwarfism gene, higher N doses promoted decrease in the variables evaluated, when compared with tall plants.…”
Section: Discussionmentioning
confidence: 99%